Catastrophic out-of-pocket payments for dental treatment: regional evidence from Spain - Samuel López-López; Raúl del Pozo-Rubio; Marta Ortega-Ortega; Francisco Escribano-Sotos (BMC, 2023)
Abstract Background To estimate the incidence and concentration of catastrophic out-of-pocket payments for healthcare and dental treatment, by region in Spain (calculated as the proportion of households needing to exceed a given threshold of their income to make these payments) in 2008, 2011 and 2015. Methods The data analysed were obtained from the Spanish Family Budget Survey reports for the years in question. The study method was that proposed by Wagstaff and van Doorslaer (2003), contrasting payments for dental treatment versus household income and considering thresholds of 10%, 20%, 30% and 40%, thus obtaining incidence rates. In addition, relevant sociodemographic variables were obtained for each household included in the study. Results With some regional heterogeneity, on average 4.75% of Spanish households spend more than 10% of their income on dental treatment, and 1.23% spend more than 40%. Thus, 38.67% of catastrophic out-of-pocket payments for dental services in Spain corresponds to payments at the 10% threshold. This value rises to 55.98% for a threshold of 40%. Conclusions An important proportion of catastrophic out-of-pocket payments for health care in Spain corresponds to dental treatment, a service that has very limited availability under the Spanish NHS. This finding highlights the need to formulate policies aimed at enhancing dental cover, in order to reduce inequalities in health care and, consequently, enhance the population's quality of life and health status.